Articulations of the Karabakh Issue in Vano Siradeghyan’s Publicist Writings - Hovakimyan, Hovhannes (Bulletin of Yerevan University B: Philology, 2025)
This article is dedicated to a systematic analysis of the reflection of the Nagorno-Karabakh conflict in Vano Siradeghyan’s journalistic writings. For Siradeghyan, the Karabakh issue was not merely a topic but served as a starting point for his publicist work and a central axis of his political biography. The article demonstrates how Siradeghyan approached the issue, simultaneously examining its historical, political, geopolitical, and domestic dimensions. The analysis focuses on Siradeghyan’s journalistic articles and speeches, in which he criticizes both the strategic shortcomings of the Armenian authorities and the manipulations of international powers. Special emphasis is placed on Siradeghyan’s view of the conflict not only as a military or political matter but also as a decisive issue of national psychology and statehood. As a result of the study, it is concluded that Siradeghyan’s journalistic work on the Karabakh conflict stands out for its historical realism, in-depth analysis, and strategic thinking—maintaining its relevance to this day.